Anionic polymerization of activated oxetane and its copolymerization with ethylene oxide for the synthesis of amphiphilic block copolymers. Issue 19 (25th April 2018) - Gervais, Matthieu; Forens, Antoine; Ibarboure, Emmanuel; Carlotti, Stephane
Abstract : The anionic polymerization of oxetane in toluene was achieved using a combination of tetraoctylammonium bromide and simple triisobutylaluminum. By its copolymerization with ethylene oxide, di- and triblock copolymers were prepared in one and two steps respectively. Abstract : The synthesis of polyoxetane (POx) and amphiphilic block copolymers composed of poly(ethylene oxide) (PEO) and polyoxetane was achieved by anionic ring-opening polymerization and monomer activation. First the anionic polymerization of oxetane was conducted using an initiating system based on tetraoctylammonium bromide associated with a simple trialkylaluminum, NOct4 Br/i-Bu3 Al (1/>1). This methodology allowed the controlled synthesis of polyoxetanes with molar masses up to 10 000 g mol −1 and a narrow molar mass distribution ( Đ < 1.2). The synthesis of diblock copolymers was achieved starting from a mixture of ethylene oxide and oxetane, thanks to their difference in reactivity. The micellization of PEO- b -POx in water was studied as a function of temperature with a shrinking phenomenon appearing at around 33 °C. Finally, a two-step procedure is also discussed for the synthesis of polyoxetane- b -poly(ethylene oxide)- b -polyoxetane triblock copolymer.